2019
DOI: 10.3390/sports7070178
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Fundamental Motor Skills in Identifying Differences in Performance Levels of U10 Soccer Players

Abstract: This study examined the differences in fundamental motor skills (FMSs) and specific conditioning capacities (SCCs) between a coach’s classification of first team (FT) and second team (ST) U10 soccer players and examined the most important qualities based on how the coach differentiates them. The FT (n = 12; Mage = 9.72 ± 0.41) and ST (n = 11; Mage = 9.57 ± 0.41) soccer players were assessed using the Test of Gross Motor Development-2, standing long jump, sit and reach, diverse sprints, and the 20 m multistage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 47 publications
5
24
0
8
Order By: Relevance
“…This pilot study indicates that the MQ total, as it has solely contributed to the canonical discriminant function, can differentiate (group centroid) POOR (−1.507), GOOD (0.032), and EXCELLENT (1.524) and that children with higher MC total levels ought to have higher levels of swimming ability (standardized canonical coefficients: POOR 1.186; GOOD 1.363; and EXCELLENT 1.535). This is in line with the previous studies which reported that higher MC levels were related to higher levels of other sport-specific motor skills in beginner karatekas [30] and youth soccer players [27,28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This pilot study indicates that the MQ total, as it has solely contributed to the canonical discriminant function, can differentiate (group centroid) POOR (−1.507), GOOD (0.032), and EXCELLENT (1.524) and that children with higher MC total levels ought to have higher levels of swimming ability (standardized canonical coefficients: POOR 1.186; GOOD 1.363; and EXCELLENT 1.535). This is in line with the previous studies which reported that higher MC levels were related to higher levels of other sport-specific motor skills in beginner karatekas [30] and youth soccer players [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, neither of them investigated the impact of MC on swimming performance nor swimming ability in preschool and school-age children and adolescents. However, several studies disclosed that higher levels of soccer- and karate-specific motor skills are related to higher levels of MC [ 27 , 28 , 29 , 30 ]. Moreover, preschool children who developed MC at higher levels were more frequently involved in physical activity, games, and sports, as compared to inactive peers [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…General motor competence is a significant long term predictor of physical performance (aerobic fitness and explosive power) in youth soccer players (Rommers et al 2018). Despite the wealth of information suggesting FMS play an important role in future sport performance, and specifically underpin performance in soccer (Jukic et al 2019), and their inclusion as key pillars in frameworks for youth movement development such as the Athletic Skills Model (Wormhoudt et al 2017), there remains a lack of research examining how FMS link with or interact with other aspects of soccer performance in young players including physical abilities and technical skills. This is despite the fact that national governing body coaching awards in soccer explicitly focus on the development of FMS within their curricula (FAI 2009;North et al 2014;The FA, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, given the increases in time that children spend in formal club academies, and the multiple benefits of developing FMS and strength from a young age 2,5,6 , it would seem imperative to examine what professional football academies (who are governed by the EPPP) are currently doing to develop such physical qualities in their young athletes, particularly in the Foundation Phase (e.g., 8-12 year olds). Indeed, Jukic et al 16 suggested that FMS competence may be associated with higher levels of technical performance in football and, consequently, football clubs should have a vested interest in developing them within their players.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Jukic et al. 16 suggested that FMS competence may be associated with higher levels of technical performance in football and, consequently, football clubs should have a vested interest in developing them within their players.…”
Section: Introductionmentioning
confidence: 99%